Ecological Distribution of Protosteloid Amoebae in New Zealand - Zahn,Geoffrey; Stevenson,Stephen L.; Spiegel,Frederick W. (PeerJ PrePrints, 2013)
During the period of March 2004 to December 2007, samples of aerial litter (dead but still attached plant parts) and ground litter were collected from study sites representing a wide range of latitudes (34° S to 50° S) and a variety of different types of habitats throughout New Zealand (including Stewart Island and the Auckland Islands). The objective was to survey the assemblages of protosteloid amoebae present in this region of the world. Twenty-nine described species of protosteloid amoebae were recorded, along with the heterolobesean acrasid, Acrasis rosea. Of the species recovered, Protostelium mycophaga was by far the most abundant and was found in more than half of all samples. Most species were found in fewer than 10% of the samples collected. Seven abundant or common species were found to display significant preferences for aerial litter or ground litter microhabitats. There was some evidence of a general pattern of a decrease in species richness and diversity with increasing latitude and precipitation and elevation.
Keywords: Amoebae; Protostelid; New Zealand; Biogeography